Embeddings, projections, and Easton’s lemma - Šárka Stejskalová (Acta Universitatis Carolinae: Philosophica et Historica)
We survey some lesser-known facts concerning properties of embeddings and projections between forcing notions. We will also state some generalizations of Easton’s lemma. To our knowledge, many of these facts have not been published, so we include their proofs for the benefit of the reader.